Interplay between internal stresses and matrix stiffness influences hydrothermal ageing behaviour of zirconia-toughened-alumina. (15th February 2020) - Wei, C.; Montagnac, G.; Reynard, B.; Le Roux, N.; Gremillard, L.
Abstract: Zirconia based bio-ceramics such as ZTA (zirconia-toughened alumina) composite are often used in orthopaedic and dental implants. The hydrothermal ageing behaviour of zirconia in humid environments is an important factor affecting the lifetime of these biomaterials. It is a tetragonal-to-monoclinic phase transformation that has been shown to be both temperature- and stress-dependant. Here, ZTA composites with zirconia inclusion particles of different sizes were prepared. The influence of zirconia inclusions on internal stresses and thus on ageing behaviour was studied by Raman micro-spectroscopy and X-ray diffraction. The results show that the ageing kinetics result from a balance between stiffer matrix and increased tensile stress in the zirconia inclusion as the local alumina fraction increase. As a result, the maximum monoclinic fraction formed after 1200 h ageing at 134 °C decreases with increasing alumina content, showing the predominance of the stabilization of tetragonal particles by a stiff matrix over their de-stabilization by tensile stress. Graphical abstract: Image, graphical abstract